Characterization and evolution of infection control practices among severe acute respiratory coronavirus virus 2 (SARS-CoV-2)–infected healthcare workers in acute-care hospitals and long-term care facilities in Québec, Canada, Spring 2020. (15th April 2022) - Carazo, Sara; Laliberté, Denis; Villeneuve, Jasmin; Martin, Richard; Deshaies, Pierre; Denis, Geoffroy; Adib, Georges; Tissot, France; Dionne, Marc; De Serres, Gaston
Abstract: Objectives: In this study, we aimed to (1) estimate the severe acute respiratory coronavirus 2 (SARS-CoV-2) infection rate and the secondary attack rate among healthcare workers (HCWs) in Québec, the most affected province of Canada during the first wave; (2) describe the evolution of work-related exposures and infection prevention and control (IPC) practices in infected HCWs; and (3) compare the exposures and practices between acute-care hospitals (ACHs) and long-term care facilities (LTCFs). Design: Survey of cases. Participants: The study included Québec HCWs from private and public institutions with laboratory-confirmed coronavirus disease 2019 (COVID-19) diagnosed between March 1 and June 14, 2020. HCWs aged ≥18 years who worked during the exposure period and survived their illness were eligible for the survey. Methods: After obtaining consent, 4, 542 HCWs completed a standardized questionnaire. COVID-19 rates and proportions of exposures and practices were estimated and compared between ACHs and LTCFs. Results: HCWs represented 13, 726 (25%) of 54, 005 reported COVID-19 cases in Québec and had an 11-times greater rate of COVID-19 than non-HCWs. Their secondary household attack rate was 30%. Most affected occupations were healthcare support workers, nurses and nurse assistants working in LTCFs (45%) and ACHs (30%). Compared to ACHs, HCWs in LTCFs had less training, higher staff mobility between working sites, similar PPE use, and better self-reported compliance with at-work physical distancing. Suboptimal IPC practices declined over time but were still present at the end of the first wave. Conclusion: Québec HCWs and their families were severely affected during the first wave of COVID-19. Insufficient pandemic preparedness and suboptimal IPC practices likely contributed to high transmission in both LTCFs and ACHs.